Which drop height is most suitable to simulate landing a floater? - Cooper, J.; Forsyth, J. R.; Morgan, N.; Steele, J. R. (Journal of Australian Strength and Conditioning, 2019)
When designing landing tasks for both training and research, it is essential that the landings tasks accurately represent the sports specific skills they aim to simulate so that these skills can be translated to the desired sport.